BIOCHEMISTRY OF DNA: A STUDY OF CHEMICAL EFFECTS ON GENE EXPRESSION - Mina Hussein Ubead; Haneen Hussein Rahim Mahdi; Haneen Abbass Majeed Abbass; Eman Maher Khalil Faisal; NoorAl-Huda Maher Khalil Faisal; Athraa Bassem Mohammed nayel (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The study of DNA biochemistry is pivotal to understanding the molecular mechanisms that govern gene expression. This research delves into the intricate chemical processes that influence DNA structure, function, and regulation. By examining the interplay between DNA and various chemical agents, such as methylating and acetylating compounds, we explore how these modifications impact gene expression. Our investigation encompasses both endogenous factors, like natural metabolic byproducts, and exogenous influences, including environmental toxins and pharmaceuticals. Through a combination of advanced biochemical techniques and computational modeling, we aim to elucidate the pathways through which chemical modifications alter gene expression patterns. This comprehensive analysis not only enhances our understanding of fundamental genetic processes but also provides insights into the development of novel therapeutic strategies for genetic and epigenetic disorders. The findings underscore the significance of chemical interactions in gene regulation and highlight potential avenues for targeted interventions in disease treatment and prevention.